2017
DOI: 10.1111/ced.13089
|View full text |Cite
|
Sign up to set email alerts
|

Validation and comparison of quality-of-life measures for topical 5-fluorouracil treatment: results from a randomized controlled trial

Abstract: Our study validated Skindex symptom, Skindex function and SCI social subscales for QoL measurement during treatment with topical 5-FU. The study could not provide evidence for construct validity of the other subscales. Skindex was more responsive than SCI in the context of 5-FU treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There were no differences between groups for the overall study period ( Table 3). (20) 86 (19) Abbreviations: AK, actinic keratosis; BCC, basal cell carcinoma; KC, keratinocyte carcinoma; SCC, squamous cell carcinoma. a Some percentages may not equal 100% owing to participant's refusal to answer the question, or identification as multiracial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences between groups for the overall study period ( Table 3). (20) 86 (19) Abbreviations: AK, actinic keratosis; BCC, basal cell carcinoma; KC, keratinocyte carcinoma; SCC, squamous cell carcinoma. a Some percentages may not equal 100% owing to participant's refusal to answer the question, or identification as multiracial.…”
Section: Discussionmentioning
confidence: 99%
“…The VAKCC Trial (Cooperative Studies Program 562) was a double-blind, vehicle-controlled trial for chemoprevention of KCs in veterans at high risk for these cancers. Detailed methods, including sample size calculations, are described elsewhere 5,9,[13][14][15][16][17][18][19][20] and in eAppendix 2 in Supplement 2. Participants with a history of at least 2 KCs in the 5 years prior to enrollment, at least 1 of which was on the face or ears, were recruited from 12 Veterans Affairs (VA) medical centers.…”
Section: Study Design and Interventionsmentioning
confidence: 99%
“…Results of other studies which reported the impact of AK treatment on HRQoL scores varied from no impact with imiquimod treatment to a temporary impact with PDT and fluorouracil. (Gholam et al, 2013, Pomerantz et al, 2017, Waalboer-Spuij et al, 2015 These studies had a short follow-up period (4 to 8 weeks) and did not compare multiple treatment modalities. The strength of our study is that data were collected in a large multicenter RCT with one year follow-up and allows for HRQoL comparison between different treatment groups.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%